Accuracy of shooting results imitation with an optoelectronic training system - Korostylova, Y.; Zanevskyy, I. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Controlling of postural and weapon stability is a distinctive feature in the sport of shooting [1]. Optoelectronic training systems provide a shooter with data and graphical information on the aiming line cross point coordinates on a target [2]. The SCATT system indicates a prognostic result of a real shot taking into account the period of time from triggering up to the instant when a pellet leaves a barrel and also a lateral motion of a muzzle because the pellet having left the barrel continues moving in the same direction as the muzzle [3]. The aim of the research is to compare pellet coordinates on a target with coordinates of the SCATT system imitation trace. The method of study includes shooting with Steyr LP-10 air pistol and 4,49 mm Finale Match pellets using simultaneous recording on the SCATT system and shooting with the pistol held in a vice and pellets from the same box. A research hypothesis is that coordinates of the imitation and pellet`s coordinates on a target are equal. Relative coordinates of the SCATT system point and the pellet mark on a target were calculated to avoid systematic errors caused with non-focus of its axis and a barrel axis on a target, and a gravitational displacement of a pellet. A statistical hypothesis is that a dispersion of the relative coordinates equals a dispersion of pellets hit coordinates shot with the viced pistol. A highly qualified female shooter made 10 shots from a 10 m distance. An initial speed of pellets (M±SD=162.2±0.6 mps) was measured with a chronoscope Combro cb-625M;k4. A shot moment (0.0031 s) was calculated as a time of pellet motion along a barrel (0.25 m) assuming a constant acceleration during the time. A distance between pairs of the pellet and imitated points in the relative coordinates was 2.52±0.72 mm. A radius from a centre of 10 shots executed with the viced pistol was 1.36±0.76 mm. Normal distribution of the two samples was accepted using Shapiro-Wilk test (p>0.1). With Fisher-Snedecor criterion, the statistical hypotheses about equal variances was accepted (p>0.620). T-test showed a large difference in the mean distances (p<0.003), i.e. the SCATT system imitation of the pellet mark on the target is not relevant enough. This could be caused by non-correct modelling of a muzzle trajectory as the trace imitation because angular motion of a barrel relative to the muzzle falsifies calculation of its lateral speed. The SCATT system measures one kinematical parameter in the sagittal and one in the transverse plane. They are vertical and horizontal coordinates on a target simulation. A relevant model of a barrel motion needs one more parameter in both of the planes, e.g. angles of the barrel axis relative to a normal line to the target plane.